PENTINGNYA PEMAHAMAN INFLASI DAN DAMPAKNYA TERHADAP KEHIDUPAN SISWA SMA/SMK - Charis Susanto; Echa Febriyanti Suparman; Nurul Wijiati (JURIBMAS : Jurnal Hasil Pengabdian Masyarakat, 2026)
The main problem faced is students' low financial literacy in dealing with rising prices of goods and services, which can affect their purchasing power and how they manage their pocket money. The purpose of this Community Service (PkM) activity was to provide students of SMK Muhammadiyah 1 Tangerang with a deeper understanding of the phenomenon of inflation and its real impact on their daily lives. The method used was interactive education. The results of this activity demonstrated that students understood economic dynamics (inflation) and inspired them to become wiser individuals in managing their finances amidst economic uncertainty.